Tradiciones renovadas (1999)
Ampliación del Ayuntamiento de Murcia, arq.Moneo; Ayuntamiento Vilaseca, arq. J.Llinas; Instituto Hispano-Luso, Zamora, arq.M.d.l.Casas; Centro Cívico Monte Hermoso, R.Ercilla
Keywords: CENTROS CIVICOS; REFUNCIONALIZACION ARQUITECTONICA; AMPLIACION; EDIFICIOS PUBLICOS; ESPAÑA; MONEO, JOSE RAFAEL; LLINÀS, JOSÉ; DE LAS CASAS, MANUEL; ERCILLA, ROBERTO